2021
DOI: 10.1159/000512218
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial-Mesenchymal Transition (EMT) as a Therapeutic Target

Abstract: Metastasis is the spread of cancer cells from the primary tumour to distant sites and organs throughout the body. It is the primary cause of cancer morbidity and mortality, and is estimated to account for 90% of cancer-related deaths. During the initial steps of the metastatic cascade, epithelial cancer cells undergo an epithelial-mesenchymal transition (EMT), and as a result become migratory and invasive mesenchymal-like cells while acquiring cancer stem cell properties and therapy resistance. As EMT is invol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
85
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(85 citation statements)
references
References 195 publications
(220 reference statements)
0
85
0
Order By: Relevance
“…Several molecules to target EMT have been or are currently in clinical trials whereas others are already in use. These include blocking of upstream pathways which promote tumorigenesis also beyond EMT by ligand-neutralizing antibodies, decoy receptors or inhibitors to block TGFb, NF-jB, EGFR, c-MET, WNT and Notch signaling (comprehensively reviewed in (Redfern et al, 2018;Dudas et al, 2020;Jonckheere et al, 2021). Due to difficulties in targeting transcription factors, i.e., EMT-TFs, directly, another promising approach is to apply modified synthetic miRNAs that interfere with EMT-TFs on a posttranscriptional level.…”
Section: Therapeutic Options To Target Emtmentioning
confidence: 99%
See 1 more Smart Citation
“…Several molecules to target EMT have been or are currently in clinical trials whereas others are already in use. These include blocking of upstream pathways which promote tumorigenesis also beyond EMT by ligand-neutralizing antibodies, decoy receptors or inhibitors to block TGFb, NF-jB, EGFR, c-MET, WNT and Notch signaling (comprehensively reviewed in (Redfern et al, 2018;Dudas et al, 2020;Jonckheere et al, 2021). Due to difficulties in targeting transcription factors, i.e., EMT-TFs, directly, another promising approach is to apply modified synthetic miRNAs that interfere with EMT-TFs on a posttranscriptional level.…”
Section: Therapeutic Options To Target Emtmentioning
confidence: 99%
“…Several molecules to target EMT have been or are currently in clinical trials whereas others are already in use. These include blocking of upstream pathways which promote tumorigenesis also beyond EMT by ligand‐neutralizing antibodies, decoy receptors or inhibitors to block TGFβ, NF‐κB, EGFR, c‐MET, WNT and Notch signaling (comprehensively reviewed in (Redfern et al , 2018 ; Dudas et al , 2020 ; Jonckheere et al , 2021 ).…”
Section: Therapeutic Options To Target Emtmentioning
confidence: 99%
“…Epithelial-to-mesenchymal transition (EMT) is a process that occurs under normal physiologic conditions such as embryonic development and wound healing. During EMT, epithelial cells lose their polarity and acquire mesenchymal-like features along with the capacity to migrate and invade other tissues ( 108 ). An increasing number of studies have reported that the change in the oxygen level in cancer microenvironments and the HIF1α-induced hypoxia signal transduction pathway acted as a vital regulator of EMT, which played a key role in hypoxia-induced cancer invasion and metastasis ( 109 , 110 ).…”
Section: Hdac5 and Oncogenetic Signaling Pathwaysmentioning
confidence: 99%
“…This review aims to present the overview of recent concepts in EMT as well as novel insights as emerged from single cell transcriptomics, and to provide a summary of the strategies attempted to target EMT in the context of fibrotic diseases. So far, multiple approaches have been proposed to target EMT: from targeting the upstream inducing signaling pathways [which has been extensively reviewed in other recent reviews ( Di Gregorio et al, 2020 ; Jonckheere et al, 2021 )] to targeting EMT-transcription factors (TFs), promoting MET, and targeting EMT-induced vulnerabilities, the last being the strategy potentially leading to the most promising outcomes.…”
Section: Emt In 2021: Novel Refinements Of An Old Conceptmentioning
confidence: 99%